Casein Kinase II in Theileriosis - Ole-MoiYoi, O.K. (American Association for the Advancement of Science, 1995)
East Coast fever is an acute, leukemia-like disease of cattle and Cape buffalo that is endemic in eastern, central, and southern Africa, where the disease causes high mortality and losses in livestock production. It is caused by the parasite Theileria parva, which infects bovine lymphocytolysis. A peculiar and fascinating feature of infections by this parasite is that it only survive in a subset of T lymphocytes, which subsequently become transformed gaining the ability to infiltrate tissues and survive indefinitely in vitro. Casein kinase II (CKII), a serine-threonine specific protein kinase that is ubiquitous in eukaryotic organisms, is increased markedly in lymphocyte cell lines from infected cattle, and it has been proposed that this is the molecular basis for the transformation. In cattle infected with T. parva, the proportion of infected lymphoblasts reaches a peak during the second or third week of infection. Lymphocytolysis of the T. parva-infected cells occurs during the third week of infection, and the infected animals usually die of massive pulmonary edema. There may be no better way to dissect mitogenic pathways of certain mammalian cells than that of finding and characterizing the roles of the essential elements usurped or selectively activated by oncogenic viruses and other transforming organisms, such as Theileria, which have had a long history of residence within the cells of their mammalian hosts.